ANALISIS KEMAMPUAN MEMBACA TEKS FIKSI PADA PEMELAJAR BAHASA PRANCIS - Silvi Satia Kemala (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2019)
This study illustrates the ability of students in understanding French fiction texts, the difficulties faced by learners and the efforts made by students to overcome the difficulties. The method used is the descriptive method. The data collection technique was carried out with literature study, test and questionnaire. The test given to students is Tes kemampuan membaca tingkat ingatan (memory level reading ability test) in the form of fiction texts in French. The questions in this test are in the form of true / false, matchmaking, and short answers. The test is given twice and for each test students are given a different fiction text. After the test, it can be concluded that the results of the study indicate that the reading ability of French learners in reading French fiction texts is quite good. This can be seen from the results of the tests of most students with an average percentage reading test score of 61.5% for the first test and an average of 69.83% for the second test.